Rolling Audit: Defensible Record Keeping - Neupane, Y; Sinha, P; Rayamajhi, P; Guragain, R (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Audit; data; record keeping DOI: 10.3126/njenthns.v1i2.4763 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.26-27